An Exploratory Study on SCRM: An Evidence from the Moroccan Automotive Industry - Elandaloussi, Zineb; Benbba, Brahim; Ameziane, Houdaifa (ExcelingTech, 2020)
Supply chain risk management (SCRM) is a relatively new topic in the field of supply chain management (SCM). It has gained a growing interest in the last two decades. Nevertheless, most of the studies have been conducted in the developed countries context. Taking into account that Supply Chain Risk (SCR) perception and management vary across countries and industries, we aim, through this qualitative study, to explore the way SCRs are perceived and managed in the Moroccan automotive industry.